Educational Psychology and Learning Styles: Adapting Teaching Methods for Student Success - Nayyar, Saroj; Verma, Shraddha; D. Kalidoss, D. Kalidoss; Yadav, Sanjay; Kashyap, Bindu; Sharma, Sarika (Journal of Neonatal Surgery, 2025)
Educational psychology can be defined as the study of improvement of education by examining the ability of the students and the appropriateness of the method used to teach them, as well as other important factors affecting the learning process. When it comes to improving the learning process as well as the achievement of the intended learning outcomes, it is crucial to understand how students learn. This study discusses the work of educational psychology together with the analysis of learning styles which is a rather popular but still rather debatable topic as well as the evaluation of such more effective methods as differentiation and activity approach. Despite concepts like visual, audio, and voyager, recent research findings are unsure regarding the effect they have on academic accomplishment. To fill this gap, this study will look at ways that helps instructional practices that focus on cognitive activities, procedures that are flexible, and those that support interaction enhancing students’ outcomes. Using the Interactive-Constructive-Active-Passive model, the paper analyzes the connection between the teaching strategies and the students’ activity and performance. Research indicates that the method of differentiation and active student participation helped in boosting the performance, interest and course retention. The study calls for a change in the current practices and provides suggestions on how teachers can design classrooms that are more effective in addressing the needs of students.